Jelly Candies with Apple Pomace—A Circular Economy Solution for a Food Processing Waste - Iuliana-Maria Enache; Liliana Ciurlă; Antoanela Patraș; Elena Leonte; Petru-Marian Cârlescu (Agriculture)
Apple juice processing by-product (apple pomace), considered as waste that generates important pollution problems, is also a rich source of bioactive compounds, including minerals, dietary fibers, phenolic compounds, and vitamins. The recovery and reuse of these valuable compounds from apple pomace into new food products combats environmental pollution, benefits the population and supports the circular economy. The current study proposes jelly candies made from apple pomace as an innovative way to valorize this by-product. The candies are analyzed from the point of view of the environmental impact and consumer acceptance. The environmental impact of the jelly candy was assessed by its carbon footprint (CF), calculated on the base of ingredients and equipment. The results showed a small CF value of 1.3946 kg CO2 for 1 kg of jelly, emphasizing its minimal environmental impact. Consumer research was carried out through an online questionnaire to assess the customer acceptance of this product, and the results revealed significant interest. These findings were considered when the consumer-oriented marketing plan was developed for this healthy, clean label, eco-friendly and sustainable jelly candy, with a view to launching it on the market. Considering the origin of the main ingredient, the reduced environmental impact, and the high acceptability of the product, it can be concluded that the analyzed jelly candy represents a good solution for apple juice processing waste recovery, which supports the circular economy.